2013
DOI: 10.1111/acps.12193
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner attitudes to clozapine initiation

Abstract: Professionals identified the dominant barriers to prescribing as being patient focussed - refusal of blood test monitoring or concerns about tolerability. Clinician fears about compliance or medical complications were also important. The development of out-patient services specifically tasked with initiating clozapine may help to increase the frequency of prescribing of clozapine earlier in treatment than is currently seen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
129
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(135 citation statements)
references
References 62 publications
(72 reference statements)
4
129
0
1
Order By: Relevance
“…Clozapine is generally initiated after ineffective courses of high-dose AP and polypharmacy, which leads to prolonged periods of active psychosis and worsens the prognosis. A survey of practitioners conducted in London by Gee et al [26] revealed the dominant barriers to clozapine prescription to be the patients' refusal of blood test monitoring and concerns about tolerability, as well as the clinicians' fears about compliance and medical complications [26]. In the present study, more patients with poorer prognosis known to be refractory to many courses of AP could receive clozapine.…”
Section: Discussionmentioning
confidence: 63%
“…Clozapine is generally initiated after ineffective courses of high-dose AP and polypharmacy, which leads to prolonged periods of active psychosis and worsens the prognosis. A survey of practitioners conducted in London by Gee et al [26] revealed the dominant barriers to clozapine prescription to be the patients' refusal of blood test monitoring and concerns about tolerability, as well as the clinicians' fears about compliance and medical complications [26]. In the present study, more patients with poorer prognosis known to be refractory to many courses of AP could receive clozapine.…”
Section: Discussionmentioning
confidence: 63%
“…However, many of the interviews lasted much longer than anticipated, suggesting that participants felt comfortable sharing their experiences. In addition, surveys of clinicians have reported similar findings (40). Third, our definition of high utilization may not reflect optimal utilization, which has not been defined.…”
Section: Discussionmentioning
confidence: 87%
“…Clozapine (Wenthur and Lindsley, 2013) is one of the most promising medications for treating refractory schizophrenia and controlling violent behaviors and risks of suicide (Fakra and Azorin, 2012). Many experts believe that a broader use of clozapine would benefit both individuals and the larger society, but clinicians are often hesitant to prescribe clozapine because of its adverse side effects (Fakra and Azorin, 2012; Freudenreich et al, 2013; Gee et al, 2014; Kelly et al, 2007; Nielsen et al, 2012; Warnez and Alessi-Severini, 2014). In fact, clozapine’s side effect risks led to its removal from the market, but it was later re-introduced because of its unique therapeutic benefits (Warnez and Alessi-Severini, 2014; Wenthur and Lindsley, 2013).…”
Section: Introductionmentioning
confidence: 99%